Prävention und Diagnostik multiresistenter Erreger - Scheithauer, Simone; Kaase, Martin (DMW - Deutsche Medizinische Wochenschrift, 2018)
Patients colonized or infected by multidrug-resistant bacteria (MDR) are entitled to the same medical treatment as other patients and infection control measures based on the current evidence are not in conflict with this aim. Recent studies indicate that the correct sampling technique is of utmost importance when screening for MRSA and usage of certain swabs might reduce the sensitivity considerably. Despite improvements in diagnostic strategies for direct MRSA detection by PCR, false positive results cannot be totally excluded. With regard to multidrug-resistant gramnegative bacteria differences between species should be emphasized to tailor infection control measures. E. g. easier transmissibility has been shown for K. pneumoniae compared to E. coli. Hospitals in Germany should strictly employ screening for carbapenemase-producing Enterobacterales as well as A. baumannii in all patients hospitalized abroad within the previous year. To avoid unnecessary social exclusion of MDR patients it must be emphasized that contact precautions are recommended for hospitals and not for long-time care facilities.
Keywords: multiresistente Erreger; MRSA; VRE; Carbapenemase-produzierende Enterobacterales